The low level of plasma vitamin C as a risk factor of preterm premature rupture of membrane - Muhammad Freddy Candra Sitepu; Ketut Suwiyoga; Anak Agung Ngurah Jaya Kusuma; I Gusti Putu Mayun Mayura; Made Darmayasa; I Wayan Artana Putra (DiscoverSys Inc., 2020)
Introduction: Preterm premature rupture of membrane (PPROM) still becomes a problem related with perinatal morbidity and mortality which is caused by multifactorial risk factor; especially strength of foetal membrane. Collagen is the main component of foetal membrane’s extracellular matrix whereas plasma vitamin C roles as a collagen biosynthesis enzyme-dependent co-factor, down-regulator activity of MMP-1, MMP-2, and MMP-9 and also as antioxidant in remodelling and preventing structural damage extracellular matrix. The purpose of this study is to prove the low plasma level of vitamin C as a risk factor for PPROM on preterm pregnancy.Method: This study was an analytical observational unpaired case-control performed from March 23rd until August 23rd 2018 at Polyclinic and Emergency Unit of Obstetrics and Gynaecology Sanglah Central General Hospital, Buleleng General Hospital, Mangusada General Hospital, Sanjiwani General Hospital, Wangaya General Hospital, and Prodia Clinical Laboratory Denpasar. The samples were preterm pregnancy women with premature rupture of membrane (PROM) as a case group and without premature rupture of membrane as a control group. The samples were taken from peripheral venous blood and level of plasma vitamin C is measured by HPLC method. The data were analysed by SPSS for Windows 20.0 version program then presented as table and narrative.Result: Forty subjects were divided into 2 groups, 20 preterm pregnancy with PROM as a case group and 20 preterm pregnancy without PROM as a control group. Characteristic subject based on maternal age, gestational age, parity of both groups was 27.4 and 26.1 years old, 31 and 31 weeks, and also 1 and 1 time (p>0.05), not significantly different. The mean level of plasma vitamin C on case and control group were 3.90 ± 1.61 dan 9.24 ± 2.31 mg/L (p=0.001). On the case group the low level of plasma vitamin C was 51 times (OR= 51; CI 95% = 7.57–343.73; p=0,001) higher than the control group.Conclusion: The low level of plasma vitamin C is a risk factor of PPROM.